Smart Anti Trip Distribution Board - Justin Akun, Jans Yerikho Justin; Ishak, Maizul (Progress in Engineering Application and Technology, 2023)
When electrical problems occur, which would result in a loss in the supply of electricity to residential buildings, power outages are a typical concern. Power continuity is crucial for household users since some items like their refrigerators, aquariums, and alarm systems need a constant supply of electricity. The earth leakage circuit breaker (ELCB) will trip if a fault occurs in the system, cutting off power to all the equipment. A short circuit, a ground fault, or overloading may all cause a problem. S To handle the issue, it is essential to design an automated system for the ELCB to reset. This project is evolving to automatically turn "ON" the ELCB when it trips and to alert people to turn it on when it trips due to an earth leakage to ground by sending SMS to the GSM. In this project, an Arduino UNO will be used to programmed a servo motor to trigger the ELCB switch automatically. The Global System for Mobile (GSM) will send data to Arduino when a short circuit or overcurrent occurs, and GSM will then send the user an SMS after three times reset count to switch “ON” the ELCB. This approach offers residents a practical method, particularly when no one is home. Furthermore, this system offers power continuity and real time notification towards the user using ESP 8266.